The effect of interrupting sedentary behaviour on the cardiometabolic health of adults with sedentary occupations - Dunning, Jason Robert (My University, 2018)
There has been an increase in the percentage of individuals employed in sedentary occupations over the last 50 years. Prolonged sedentary time has been associated with poorer cardiometabolic health. Interrupting prolonged sedentary activity may attenuate the risk of developing cardiometabolic disease. This study aimed to determine whether prompts delivered via a mobile phone were effective in reducing sedentary behaviour (measured objectively using an Actigraph and activPAL accelerometer) in people with sedentary occupations. Twenty men and women were randomly assigned to either a control or intervention (PROMPT) group. Only participants in the PROMPT group were instructed to interrupt their sedentary behaviour. During the intervention participants in the PROMPT group spent less time in sedentary behaviour (5.5±0.5 hrs/day) during their working day, compared to the control group (6.7±0.6 hrs/day) as measured using the activPAL (p=0.04). There was no association between the intervention and cardiometabolic health variables. There were differences in the outputs of ActiGraph and activPAL accelerometers. Interrupting prolonged sedentary time via mobile phone messages may be an effective strategy in reducing total sedentary time in the workplace.
A dissertation submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Master of Science in Medicine Johannesburg, 2018.
Keywords: Cardiometabolic Health; Sedentary Behavior